Rivate Sector Involvement in Clean Water Management: Appointment of PT Moya Indonesia By the DKI Jakarta Provincial Government (2022) - Pangihutan, Risto Mulia; Angela, Deni (Journal of Law, Politic and Humanities, 2024)
The privatization of clean water in DKI Jakarta has presented major challenges in providing quality and affordable clean water services for the community. This article discusses the various challenges faced, such as high levels of pipe leaks, low water quality, and limited infrastructure. However, there is also hope to improve clean water services by accelerating the increase in service coverage, increasing the efficiency of water distribution management, and increasing transparency and accountability in clean water management. The active role of the DKI Jakarta DPRD and Civil Society Organizations (CSOs) is also needed to ensure better clean water management in the future. The DKI Jakarta Provincial Government must be committed to overcoming these various challenges by involving all stakeholders and strengthening cooperation between the public and private sectors in order to achieve better and more equal access to clean water for all DKI Jakarta residents.